IMF Research Bulletin, March 2016. (IMF Research Bulletin; IMF Research Bulletin ;, 2016)
The IMF Research Bulletin includes listings of recent IMF Working Papers and Staff Discussion Notes. The research summaries in this issue are 'Explaining the Recent Slump in Investment' (Mathieu Bussiere, Laurent Ferrara, and Juliana Milovich) and 'The Quest for Stability in the Housing Markets' (Hites Ahir). The Q and A column reviews 'Seven Questions on Estimating Monetary Transmission Mechanism in Low-Income Countries' (Bin Grace Li, Christopher Adam, and Andrew Berg). Also included in this issue are updates on the IMF's official journal, the IMF Economic Review, and recommended readings from IMF Publications.